The Special is Women: Suatu Ritual Adat Masuk Minta di Tanimbar Provinsi Maluku - Matelda Wearulun; Yurulina Gulo (Universitas Negeri Medan, 2020)
This paper aims to describe a traditional ritual in Tanimbar-Maluku, which is the ritual of asking for requests or applications with its own uniqueness in which the position and value of women are very high because they have a special room that no one can find, with this ritual, women's existence is in the spotlight both in the scope of the family and society in dealing with polemic about the position of women today. The problem in this paper is focused on the value of women in adat which can be implemented or equated with the reality of social life so that the position of men and women can be equal. To approach this problem the theoretical references from the theory of cultural structuralism and the theory of postmodern feminism are used to collaborate between interconnected cultural and feminist roles. The data is collected through observation and interview results from the informant descriptively ... and the data analysis conducted is qualitative analysis. The results obtained are ritual entrance asking to pay attention to the position and values of women; it is not arbitrary to get women (Tanimbar) so this paper provides a concrete contribution that reconstructs the understanding of women's position and values in cultural and social contexts so that there is a balance between men and women.